Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13104-019-4418-6
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects of a free, healthy school meal on overall meal frequency among 10–12-year-olds in Norway: the School Meal Project

Abstract: Objective To evaluate possible effects of intake of a free, healthy school meal on overall meal frequency among 10–12-year-olds in Norway. This was evaluated using a quasi-experimental school-based intervention study assessing children’s meal frequency retrospectively using a questionnaire in two elementary schools in the southern part of Norway in 2014/15. Multiple logistic regression analyses with breakfast, lunch, dinner, supper as dependent variables were used. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…A study by IlløKken et al assessed students ages 10–12 in an intervention school offering free school lunch (compared with a control group comprised of students at the same school and an additional control school) and found that free school lunch was positively associated with healthy food scores after six months of exposure, primarily due to increased consumption of fruits, vegetables, and fish spread [ 75 ]. In a separate report of results after following the same students for a year, Vik et al found that healthy food scores remained significantly higher in the intervention group compared with the control group [ 76 ], but there were no significant changes in overall meal frequency (e.g., frequency of eating breakfast, lunch, or dinner on weekdays) [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study by IlløKken et al assessed students ages 10–12 in an intervention school offering free school lunch (compared with a control group comprised of students at the same school and an additional control school) and found that free school lunch was positively associated with healthy food scores after six months of exposure, primarily due to increased consumption of fruits, vegetables, and fish spread [ 75 ]. In a separate report of results after following the same students for a year, Vik et al found that healthy food scores remained significantly higher in the intervention group compared with the control group [ 76 ], but there were no significant changes in overall meal frequency (e.g., frequency of eating breakfast, lunch, or dinner on weekdays) [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…A control group ( n = 109) continued bringing packed meals from home as usual. The intervention was evaluated using both quantitative and qualitative methods with the findings from the former reported elsewhere ( 5 , 23 , 26 ). This paper reports an analysis of interviews with students and teachers that were carried out immediately post-intervention (2015), and follow-up interviews with teachers and students carried out 5 years later in 2020.…”
Section: Methodsmentioning
confidence: 99%
“…As provision of meals at school has become a political priority in Norway, studies on the introduction and evaluation of school meals in Norway are increasing [32,[34][35][36][37]62]. However, there is a lack of studies including a wide sample of pupils, teachers and parents.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In Norway, there have been several initiatives and pilot projects to test different school meal models and how school meals could be implemented [30,31]. The few intervention studies that have been conducted have generally shown an association with a healthier diet [28,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%